Dynamic compressive properties of heat-treated and pre-stressed cement mortar specimen subjected to cyclic impact loading - Ronghua Shu; Guang Xu; Lijinhong Huang (Case Studies in Thermal Engineering, 2024)
By carrying out the cyclic dynamic compressive experiment, the dynamic compressive properties of heat-treated and pre-stressed cement mortar subjected to cyclic impact loading were obtained. The results show that under static and cyclic impact loading, the peak stress shows a nonlinear decrease trend with the increasing dynamic impact number, and the failure strength decreases as heated temperature increases. The strain rate shows a linear increase trend as impact number increases. The relationship among the strain rate, temperature and impact number obey exponential relations, which could be expressed as ε˙ = 0.64e0.00854T＋4.93 × 10−3Tn＋0.77n＋18.70. The strain rate increase factor could be calculated by temperature by ω = 1.04＋3.37 × 10−2e0.00849T. The impact number almost decreases linearly with the increasing temperature. The peak strain exhibits an increasing trend with an increase in impact number and temperature. The specimens are destroyed at a damage value of around 0.68 to 0.74. When the heated temperature increases, the failure size of pieces of specimen decreases accordingly. The fragmentation rate follows exponential function with temperature, which could be calculated by η = 0.325 + 5.55 × 10−5e0.0314T. The total reflected energy increases, and total transmitted energy, absorbed energy and accumulated absorbed energy per volume decrease as temperature and impact number increase.